Observation and practical implications of nano‐scale phase separation in aluminosilicate glass optical fibers. Issue 3 (12th October 2018) - Cavillon, Maxime; Dragic, Peter; Greenberg, Bennett; Garofalini, Stephen H.; Ballato, John
Abstract: This communication provides direct experimental evidence of nano‐scale phase separation in as‐fabricated high‐alumina content (>25 mole percent) optical fibers, experimentally corroborating recent molecular dynamic simulations. In addition, previously incorrect assumptions of glass homogeneity in low‐loss binary aluminosilicate optical fibers are corrected and practical implications for such intrinsically low nonlinearity glass optical fiber amplifiers and lasers are discussed.